Ação do extrato de glândulas salivares de fêmeas do carrapato Rhipicephalus sanguineus (Latreille, 1806) sobre a inibição da proliferação de células de linhagem tumoral - Anholeto, Luís Adriano [UNESP] (2015)
Ticks, hematophagous ectoparasites produces saliva that presents molecules capable of modulating the immune-inflammatory and hemostatic system of the host. The present study was performed to characterize the salivary gland extract of female Rhipicephalus sanguineus (Latreille, 1806) fed for four days in rabbits by mass spectrometry (LCMS-IT-TOF) by shotgun strategy, which identified 14 proteins with diverse functions: as structural components of cell junctions, cytoskeleton, the nucleosome, and protein with anticoagulant and antiinflammatory actions corroborating data in the literature. In this study, we attempted to also examine the antitumor potential of this extract on tumor cell lines SK HEP-1 and HEP-G2, by MTT assay; analysis by Laser Scanning Confocal Microscopy techniques, and pattern analysis of mRNA transcription involved in cell death by apoptosis, including the products of genes Bax, Bcl-2, Caspases 3 and 9 Fas and Interleukin-1 α. The results showed that the extract obtained in concentration of 50 μg/ml significantly inhibited the proliferation of both cell lines tested. In the analysis of cores and actin filaments, of the treated cells were not observed morphological characteristics that indicate cell death processes by apoptosis. The analysis of the pattern of transcription of mRNAs involved in mechanisms of cell death by apoptosis, showed a significant expression of some apoptotic genes, in treated cells compared to the control group, suggesting that the action of the extract can cause an unbalance homeostasis in the cell, which can trigger processes of cell death by apoptosis, confirming the data presented in the literature